Ecosystems and human well-being : (Island Press, 2005)
The Sub-global Assessments Working Group integrated information from multiple sources and found that biophysical factors such as land-use change, climate change and variability, pollution, and invasive species have a significant effect on human well-being across cultures. For example, in places where there are no other social safety nets, diminished human well-being tends to increase immediate dependence on ecosystem services, which can damage the capacity of those local ecosystems, which in turn appears to increase the probability of natural disaster or conflict.